The bastard of Istanbul - "Shafak, Elif" (Penguin Books London, 2007)
The Bastard of Istanbul by Elif Shafak is a multilayered novel that explores themes of identity, memory, and the complexities of Turkish-Armenian history. The story revolves around two families one Turkish and one Armenian-American whose lives are connected by a hidden past. The novel primarily follows Asya Kazancı, a rebellious young woman growing up in Istanbul, and her Armenian-American cousin, Armanoush Tchakhmakhchian. As Armanoush visits Turkey to explore her ancestral roots, the two women uncover long-buried family secrets related to the Armenian genocide, cultural identity, and intergenerational trauma. Through its vibrant characters and richly detailed setting, the novel addresses themes of guilt, denial, and the collective memory of national history, while offering a poignant exploration of personal and collective identities. Shafak weaves these narratives together to create a story that is both personal and political, blending humor, emotion, and historical reflection.